An exploration of factors which enabled student learning in the SHAWCO service-learning program at UCT - Mzizana, Lungisa (School of Education, 2023)
My study is situated within the context of the increasing internationalisation of Higher Education (HE) which has become significant in a globalised society. Academic Institutions are required to produce graduates that can fit into different environments across the globe, with cross-cultural awareness and an understanding of the complexity of a globalised world. Global education has become important in promoting and facilitating the acquisition of these graduate attributes. Therefore, understanding student learning experiences in global education programs is vital for university academics, adult educators and organisations involved in the field. This study explores student's learning experiences in a SHAWCO service-learning (SSL) program at the University of Cape Town (UCT) for five international students. The SSL program hosts international students and integrates formal and informal learning. Learning takes place in many different sites such as learning in lectures, educational site visits and in community-based organisations. The program design allows international students to explore South African history, contemporary issues, and the complexities of transitioning into a democratic state. The aim of the study is to understand factors that enhanced learning for five international students who were part of the SSL program at UCT between 2016 and 2018. The study explores mixed pedagogical practices and their influence in the learning process. John Dewey's experiential theory (1938) and David Kolb (1984) who deepened experiential theory by developing a conceptual framework of cycles of learning and reflection are used in the discussion and analysis of the findings. Paulo Freire' s (1970) critical pedagogy is drawn on as his dialogical methods influenced the design of the SSL program and feminist theory which provides a critique to experiential learning. The study makes links with similar research such as Coryell (2011, 2013) and Pipitone (2017, 2018). In addition, South African studies including McMillan's (2011) study on service learning as a boundary between the university and communities, and Gredley's (2013) study on making sense of student's learning through service learning. A qualitative case study design was used to gather data through interviews from five US students who formed part of the SSL program and document analysis. The students were interviewed in their home country. The interviews took place using Voice over Internet Protocol (VoIP). This technology is used to send voice and video in real time. An interpretive approach was used to analyse experiences to give a deeper and an extensive representation of student learning experiences in the program. The findings indicate that students' learning was enhanced by the dialogical and reflective learning methods used which democratised learning and allowed for critical engagements. The study illustrated the value of pedagogical practices which integrate formal and informal learning, in the lecture, education site visits and in incidental experiences. The conclusion is that these pedagogical tools allowed students to learn intensely about South Africa's history and challenges in a new complex democracy.